ANALISIS KUALITATIF KEMAMPUAN MAHASISWA PGSD DALAM MENGEMBANGKAN MODUL AJAR KURIKULUM MERDEKA - Dwi Widyastuti Nurharyanto (PEDAGOGIK, 2023)
This research is qualitative descriptive research. This study aims to see the extent to which PGSD, FKIP, Khairun University students are capable of preparing Teaching Modules. The instrument used is an instrument in the form of a test. Of the three main components, it was found that students had insufficient knowledge of the enrichment components and worksheets. The average of the results obtained is the general information component of 99.3%, the initial component is 97.3%, and the attachment is 44%. Three main components are used as benchmarks, namely the general information component, the initial component, and the attachments. Both of these components get a percentage of 44% or as many as 11 students do not understand these components so they are not included in making the Teaching Module. There is a need to deepen the material again for students to master making good Teaching Modules. Teaching Modules as a form of planning will also have an impact on learning processes and outcomes.